Counting Cell Divisions: A Computational Approach Using DNA Tandem Repeats - Regolini, Marco Franco Giulio (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Repetitive DNA occurs in all domains of life—Bacteria, Archaea and Eukaryota—and can be grouped into two categories: interspersed repeats, such as transposable elements occurring in multiple loci across the genome, and tandem repeats (TRs) that occur in a single locus. This manuscript presents a compelling exploration of the role of DNA tandem repeats (TRs) in counting cell divisions, employing a computational model that could significantly advance the understanding of cell biology and epigenetics. The integration of TRs as iterable objects not only offers a fresh perspective but also provides a potential framework for investigating fundamental biological processes. The research could pave the way for novel insights into cellular mechanisms and their implications for development and disease. Overall, this manuscript aims to be a contribution to the scientific community, encouraging deeper discussions about the noncanonical roles of TRs in genomic regulation.